Predicting the anterior-posterior component of ground reaction force from wearable instrumentation - Billing, D. C; Hayes, J. P.; Baker, J.; Nagarajah, R. C. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Force platforms, embedded in the surface of a runway, are the 'gold standard' contact measurement technique for the collection of ground reaction force (GRF) data during running. However, this technique requires that data is collected in a laboratory environment and factors such as targeting and limited successive foot contacts restrict the knowledge that can be gained by this form of instrumentation. In recent years the availability of miniature electromechanical transducers suitable for the construction of wearable instrumentation have become available. Such transducers have been used to measure the distributed GRF at the foot-shoe interface (in-shoe pressure) and measure acceleration in three orthogonal components from a site approximating the subject's centre of mass (CoM acceleration). However, there are a number of difficulties in relating measurements from these transducers to anterior-posterior (AP) GRF as their output is not directly related to this component of GRF and the transducers themselves are mediated by the subjective conditions in which they are applied. The findings indicate that the AP component of GRF can be predicted from wearable instrumentation and provides the possibility of determining braking and propulsive forces in a competition and training environment, which is currently not possible.